Genetic diversity and symbiotic efficiency of legume nodulating bacteria from different land use systems in taita taveta, kenya - Mwangi, Simon N.; Karanja, Nancy M.; Boga, Hamadi M.; Kahindi, James M.; Muigai, A.M.; Odee, D.; Mwenda, George M. (2011)
Populations of Legume Nodulating Bacteria (LNB) were assessed under glasshouse conditions in soils collected from selected landuse systems in Taita Taveta district, Kenya. The populations were estimated by the most-probable-number (MPN) plant infection technique using Macroptilium atropurpureum (DC.) Urban (siratro) as the trap plant. The LNB populations varied from 1.1 × 10 to 6.1 × 106 cells g-1 of soil. There was apparent landuse effect on abundance of LNB with maize-bean cropping system and shrubland giving high population estimates. Two thousand isolates of LNB were obtained from the nodules of siratro trap plants . These isolates were characterized on yeast extract mannitol mineral salts agar (YEMA) media containing bromothymol blue and two distinctive rhizobia fgroups namely 21.4% being fast growers (acid-producing) and 79% slow growers (alkali-producing) identified. Symbiotic effectiveness of a selected number of the isolates ranged from 6.7% to 95.4% and no clear influence of landuse was observed. RFLP of amplified 16S rRNA genes of isolates with HaeIII and TaqI grouped the isolates into seven ribotypes and partial sequencing of 16S rRNA genes of isolates representative of the ribotypes further grouped the isolates into six genera namely; Sinorhizobium, Bradyrhizobium, Herbaspirillum, Agrobacterium, Rhizobium and Burkholderia. Landuse type was found to significantly influence the diversity of LNB